2013
DOI: 10.5539/ass.v9n15p214
|View full text |Cite
|
Sign up to set email alerts
|

Parental Attachment, Peer Attachment, and Delinquency among Adolescents in Selangor, Malaysia

Abstract: This study aimed to investigate the relationships between parental attachment, peer attachment and delinquency among adolescents. 480 adolescents aged 13-17 were randomly selected from four secondary schools in Malaysia. The revised version of the Inventory of Parent and Peer Attachment (IPPA) (Armsden & Greenberg, 1987) and the Self-report Delinquency Scale (Mak, 1993) were used in this study. The results revealed significant negative relationship between father and mother attachment with adolescents' delinqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 19 publications
2
19
0
Order By: Relevance
“…Findings indicated that when adolescents are highly attached with their parents, they have lower tendency to involve themselves in antisocial behavior. The finding is consistent with past studies which found that adolescents are less likely to engage in delinquent and aggressive behavior when they are attached to their parents (Lim et al, 2013;Gallarin & Alfonso, 2012;Nooshin et al, 2013). The findings on coping efficacy and antisocial behavior supported past evidence which noted that adolescents who are able to cope with negative emotions are less likely to engage in aggressive behaviors (Downey et al, 2010).…”
Section: Conclusion Implications and Significancesupporting
confidence: 92%
See 1 more Smart Citation
“…Findings indicated that when adolescents are highly attached with their parents, they have lower tendency to involve themselves in antisocial behavior. The finding is consistent with past studies which found that adolescents are less likely to engage in delinquent and aggressive behavior when they are attached to their parents (Lim et al, 2013;Gallarin & Alfonso, 2012;Nooshin et al, 2013). The findings on coping efficacy and antisocial behavior supported past evidence which noted that adolescents who are able to cope with negative emotions are less likely to engage in aggressive behaviors (Downey et al, 2010).…”
Section: Conclusion Implications and Significancesupporting
confidence: 92%
“…Adolescents who reported positive attachment with parents were less delinquent (Lim, Muslihah, Sa'odah, & Wu, 2013) and used more active coping strategies (Locke & Zimmer-Gembeck, 2007). Longitudinal study found that improvement in mother-child relationship contributed to the development of coping efficacy and active coping among children (Velez, Wolchik, Tein, & Sandler, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The subscales of Compassion for self (positive emotions) has 15 items, Compassion from others has 13 items and lastly, Compassion towards Others has 10 items [36]. 4. Inventory of Callous-unemotional traits -Youth [54] is a scale that assesses the three themes within the Callous-unemotional trait, namely: uncaring, unemotional and callousness.…”
Section: Methodsmentioning
confidence: 99%
“…Studies were conducted within the country to understand the causes of misdemeanor by juveniles. One of the trends found in juvenile delinquents is mostly poor relationships with their parents [4,5], supported by a meta-analysis on the attachment of parent, peer and child, with delinquency [6]. It appears that situations of deficits in receiving affection and companionship by caregivers that occur concurrently in juvenile delinquents are in need of further studies [7].…”
Section: Introductionmentioning
confidence: 99%
“…Capaldi and Shortt (2003) explained that delinquent behavior is included in the classification of abnormal behavior. Delinquent behavior may start from a less severe wrongdoing, for instance violation of school rules such as truancy, smoking and vandalism to more serious crimes such as theft, robbery, drugs, rape, possessing weapons (Choon, Hasbullah, Ahmad, & Ling, 2013;Jung & Choi, 2017), sexual activities, baby dumping, illegal racing (Sh Marzety Adibah, Melati, & Zuria, 2013) and the list goes on.…”
Section: Introductionmentioning
confidence: 99%